The Relationship between Liberalism and Human Values Based on Public Interest: Moral Understanding of Social Responsibility - Shiva Yousefi; Bahman Banimahd; Hashem Nikoomaram (International Journal of Ethics and Society, 2024)
Introduction: Social responsibility from an ethical point of view includes the obligations and duties of natural and legal persons towards society and the environment. The moral behavior of people, like understanding of social responsibility, depends on their liberal ideology, beliefs and human values. Therefore, the aim of the current research is to study the relationship between liberalism and human values with the moral understanding of social responsibility. Material & Methods: The research method is applied in terms of purpose and descriptive-correlational survey. The statistical population includes the financial managers of the companies admitted to the stock exchange, and the questionnaire was randomly distributed among them and 110 questionnaires were received. The sampling method is random. The research tool is a questionnaire and multivariate regression using SPSS software was used to analyze the data. Results: The research results show that human values based on public interest have a significant and positive relationship with the moral understanding of social responsibility. But the thinking of liberalism does not have a meaningful relationship with the moral understanding of social responsibility. Conclusion: Based on the findings of this research, human values based on public interest can be considered as a tool to strengthen the moral behavior of company managers regarding corporate social responsibility. Also, improving the thinking of liberalism in managers can strengthen their social responsibility. In this case, the policy makers of Stock Exchange can direct the managers of the listed companies to comply more with the social responsibility of the company, through teaching human values and strengthening those values, as well as monitoring the implementation of ethical regulations